The impact of cash transfers on local economies - Michael MacLennan; Stephanie Levy (International Policy Centre for Inclusive Growth (IPC-IG), 2015)
In this special edition of Policy in Focus, leading authors and practitioners present their research on how cash transfers can impact the local economy when implemented in a developing country. The aim is to gather and review research results and evidence, obtained from various methodologies ranging from randomised control trials (RCTs) to village economy models and general equilibrium analysis, applied on small-scale programmes to larger-scale policies in Latin America, Africa and South-East Asia. The economic impact of social transfers is analysed here through their effects on investment, productivity, prices, employment and trade and through more general equilibrium effects of redistributive policies. [...]
Keywords: 330; Impact; Cash Transfers; Local Economies